Extraction composition, extraction system and application method of extraction composition - YUAN CHENGYE; LI JINFENG (2018)
The invention discloses an extraction composition, an extraction system and an application method of the extraction composition. The extraction composition comprises an extraction agent and a neutralphosphorus oxide compound shown as the formula A. The extraction agent contains N,N-dicyclohexyl benzamide and does not contain N,N-disposed(2-ethylhexyl)acetamide. A mixture of an amide compound of aspecific structure and the neutral phosphorus oxide compound are selected as the extraction composition. The extraction rata of the extraction composition on Li contained in Li-containing brine is 81% or more, like 81.53%-94.69%. The Li-Mg distribution coefficient reaches up to 490 or more, like 490-987. When Li is reextracted through HCl, the reextraction rate is 87.86%-91.68%. The extraction and reextraction performance of the extraction composition extracting Li salt from the Li-containing brine is greatly improved. The extraction composition is cost-saving and more suitable for industrialproduction. 本发明公开了种萃取组合物、萃